Government records about the Australian Capital Territory - Ling, Ted; National Archives of Australia ([Canberra Business Centre, Australian Capital Territory] : National Archives of Australia, 2013)
"Government Records about the Australian Capital Territory was produced by the National Archives of Australia and ArchivesACT as part of the Canberra 100 celebrations. The year 2013 marks a century since the official naming of Canberra as the nation's capital. Meticulously researched and extensively referenced, this research guide provides a comprehensive overview of the administrative history of the ACT, its people, important activities and events in the twentieth century. Along with historical narrative, it contains records listings from the National Archives, ArchivesACT and other relevant collecting institutions. Structured according to functions that are primarily the responsibility of the Australian Government or ACT Government, Government Records about the Australian Capital Territory delves into the unique history of the Territory, from the perspective of a diverse range of subject areas. It is an invaluable tool in the search and discovery of archival records relating to the history of the Territory.." -- cover description.
At foot of title: "National Archives of Australia".
Includes bibliographical references and index.
Also available in electronic format via the Internet. Address as at 7/11/13
Keywords: National Archives of Australia -- Catalogs; Public records -- Australian Capital Territory -- Bibliography -- Catalogs; Public records -- Australia -- Bibliography -- Catalogs; Australian Capital Territory -- History -- Sources -- Bibliography -- Catalogs; Australian